Risk factors for surgical site infection following craniotomy: a 10-year retrospective cohort study - Hojka Rowbottom; Borut Hribernik; Janez Ravnik (Acta Medico-Biotechnica, 2022)
Purpose: A craniotomy is a common surgical procedure with complications, including a surgical site infection after craniotomy (SSI-CRAN), for which risk factors are ill-defined. Therefore, we determined the risk factors for developing an SSI-CRAN in adult patients at a university hospital in Maribor.Methods: A retrospective cohort study was conducted to compare patients with an SSI-CRAN (n=66) against a control group (n=70) from January 2009 to August 2019. We collected data from patients in who elective craniotomy had been performed and required surgical treatment for an infection.Results: A total of 1192 patients underwent a craniotomy, of whom 66 (5.5%) developed an SSI-CRAN. The most common infections were osteomyelitis (66.7%) and epidural abscesses (63.6%). The most frequent causative organism was Propionibacterium acnes (54.5%). Based on Fisher’s exact test, the factors associated with an SSI-CRAN compared to the control group were use of Surgicel® (89.4% vs. 67.1%, p=0.0019), use of dural substitutes (53% vs. 27.1%, p=0.0028), use of adhesive dura (13.9% vs. 2.9%, p=0.0274), sutures used for skin closure (69.7% vs. 34.3%, p=0.0001), a frontal craniotomy (28.8% vs. 12.9%,p=0.0328), and postoperative administration of glucocorticosteroids (73.7% vs. 54.4%, p=0.04).Conclusion: We identified risk factors associated with SSIs-CRAN, for which alternatives exist that could reduce the incidence of SSIs-CRAN.